Guru Chethana : A Unique Initiative of Government of Karnataka in Teacher Professional Development - Periodi, Umashanker; Rudresh S (Voices of Teachers and Teacher Educators, 2018)
All of us aspire for a good society that is just, equitable, humane, and sustainable. It is assumed that school education provides the foundation for it. It is believed that Education could bring such a society through non-violent and sustained manner. Both central and state govt. have put their best efforts to ensure easy access of school for all the children and have successfully promoted regular attendance through various govt. programmes. India did achieve quite a lot in terms of enrolment, and attendance of students in primary schools. Many popular large scale reports such as ASER, NAS have identified gaps in learning levels of students across the subjects. Among all the factors like infrastructure, PTR (Pupil Teacher Ratio), socio-economic condition of the parents, the culture of the larger community which impact education, the quality of the teacher has a major impact on the quality of education in school. The quality of education is considerably determined by the quality of the teachers and their engagements in the classroom. Teachers professional abilities eventually contribute to the quality education in schools.